2021
DOI: 10.1007/s42773-021-00089-z
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effects of hydrochar application rate on soil amelioration and plant growth in three diverse soils

Abstract: The hydrothermal carbonization (HTC) of biogas digestate alters the raw materials inherent characteristics to produce a carbon (C)-rich hydrochar (HC), with an improved suitability for soil amelioration. Numerous studies report conflicting impacts of various HC application rates on soil properties and plant growth. In this study, the influence of HC application rate on soil improvement and plant growth aspects was investigated in three diverse soils (Chernozem, Podzol, and Gleysol). Pot trials were conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The S3 substrate exhibits the highest plant growth, probably because of the high OM content of peat, which, in combination with vermiculite, provides higher moisture retention and aeration. These results highlight the importance of choosing an adequate type of char material for each crop, plant, and soil [31]. Regarding the FHC concentration, we found that plants growing in S3 suffer a soft growth inhibition as the dose increases, while in the other substrates, a significant decrease in leaf area is observed in comparison with the control.…”
Section: Germination and Growth Tests Using Peat-based Substrates Wit...mentioning
confidence: 59%
See 1 more Smart Citation
“…The S3 substrate exhibits the highest plant growth, probably because of the high OM content of peat, which, in combination with vermiculite, provides higher moisture retention and aeration. These results highlight the importance of choosing an adequate type of char material for each crop, plant, and soil [31]. Regarding the FHC concentration, we found that plants growing in S3 suffer a soft growth inhibition as the dose increases, while in the other substrates, a significant decrease in leaf area is observed in comparison with the control.…”
Section: Germination and Growth Tests Using Peat-based Substrates Wit...mentioning
confidence: 59%
“…Moreover, addition of compost to the hydrochar diminished the phytotoxicity on cress seeds and Chinese cabbage germination [2,29]. Nevertheless, further research is needed to understand the relationship between the characteristics of hydrochar and the responses of different crops linked to soil type and dosage [30,31], time of stabilization [2], and the effect of post-treatments prior to soil application.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, those hydrochars from acid-free HTT would be suitable as a solid organic fertilizer because they contain N, P, and K, and those from HCl-mediated HTT would be suitable as soil amendment (nutrients have been mostly extracted) (Table S1). However, beyond complying with the limits established by current regulations, some authors have reported that the presence of certain organic compounds in hydrochars could inhibit plant growth, highlighting the importance of conducting studies to ensure proper synergy between HTC products and plant metabolism. , Eskandari et al (2019) tested the effects of paper mill sludge-based hydrochar on pine seedling growth, reported that the application of adequate rates of hydrochar can reduce fertilizer requirements, and showed positive effects on germination, shoot biomass, and stem diameter compared with control seedlings (without hydrochar) under the fertilizer levels tested.…”
Section: Resultsmentioning
confidence: 99%
“…8 An alternative utilization of hydrochar as a soil amendment/fertilizer is also obstructed due to the phytotoxicity of N-heterocycles toward plants. 9 In addition, the existence of N-heterocycles in the nutrient-rich aqueousphase coproduct also complicates the nutrient separation using a membrane due to the potential fouling and blockage of the membrane pores. 10 These disadvantages demonstrate the importance of suppressing the formation of N-heterocycles in order to increase the techno-economic attractiveness of HTL operation.…”
Section: Introductionmentioning
confidence: 99%
“…While N-heterocycles removal from biocrude is possible via the catalytic hydrotreatment process in traditional oil refineries, the additional cost of this upgrading step leads to operational expenditure surpassing the economical price of the produced drop-in fuel . An alternative utilization of hydrochar as a soil amendment/fertilizer is also obstructed due to the phytotoxicity of N-heterocycles toward plants . In addition, the existence of N-heterocycles in the nutrient-rich aqueous-phase coproduct also complicates the nutrient separation using a membrane due to the potential fouling and blockage of the membrane pores .…”
Section: Introductionmentioning
confidence: 99%